(untitled) (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted at the Mushroom growth house and Tissue Culture Laboratory, Horticulture Demonstration and Training Centre (HDTC), Kewatkhali, Mymensingh during February to May, 2006 to investigate the effect of different substrate on growth and yield of Button mushroom (Agaricus biporus). The substrates which were used in the experiment were wheat: paddy (1:1) straw compost, paddy straw compost and decomposed cowdung. The parameters observed in first and second flush were number of primordia, number of fruiting bodies and fresh weight of mushroom. Data were statistically analyzed following Completely Randomized Design (CRD). Data revealed that different substrate significantly affected the production of number of primordia, number of fruiting bodies and fresh weight. In both the first and second flush, all the three observed parameters were obtained highest in wheat: paddy straw compost and the lowest were in decomposed cowdung. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14810 J. Environ. Sci. & Natural Resources, 5(2): 177-180 2012